Subcritical water technology for enhanced extraction of biochemical compounds from Chlorella vulgaris - Awaluddin, Saidatul Aliaa; Thiruvenkadam, Selvakumar; Siajam, Shamsul Izhar; Yoshida, Hiroyuki; Danquah, Michael Kobina; Harun, Mohd Razif (Hindawi Publishing Corporation, 2016)
Subcritical water extraction (SWE) technology has been used for the extraction of active compounds from different biomass materials with low process cost, mild operating conditions, short process times, and environmental sustainability. With the limited application of the technology to microalgal biomass, this work investigates parametrically the potential of subcritical water for high-yield extraction of biochemicals such as carbohydrates and proteins from microalgal biomass. The SWE process was optimized using central composite design (CCD) under varying process conditions of temperature (180–374°C), extraction time (1–20 min), biomass particulate size (38–250 μm), and microalgal biomass loading (5–40 wt.%). Chlorella vulgaris used in this study shows high volatile matter (83.5 wt.%) and carbon content (47.11 wt.%), giving advantage as a feedstock for biofuel production. The results showed maximum total carbohydrate content and protein yields of 14.2 g/100 g and 31.2 g/100 g, respectively, achieved under the process conditions of 277°C, 5% of microalgal biomass loading, and 5 min extraction time. Statistical analysis revealed that, of all the parameters investigated, temperature is the most critical during SWE of microalgal biomass for protein and carbohydrate production.